University students’ beliefs about errors predict their willingness to take academic risks - Hübner, Vanessa; Pfost, Maximilian (Frontiers in Education, 2022)
Students’ beliefs about errors have become a field of interest within higher education research. Studies show that these are associated with students’ GPA as well as their learning strategies. Whether students’ beliefs about errors are associated with their willingness to engage in learning situations in which making errors is likely, is still an open question. To address this research gap, we measured error beliefs on three dimensions (affect, cognition, and behavior) on a sample of N = 159 university students. Applying stepwise linear regression and using academic risk taking as dependent variable for learning behavior that is characterized by a risk of making errors, this article shows that beliefs about errors influence students’ willingness to engage in error-prone situations within seminar settings. Students who do not show negative affect after making errors tend to take more academic risks within seminar settings, and students who are behaviorally apt to work with their errors take less academic risks. In contrast, beliefs about errors do not seem to relate to students’ engagement in academic risks in front of their peers. These results contribute to a deeper understanding of the role of students’ beliefs about their errors for educational dynamics and processes. They also offer implications for practitioners such as promoting strategies for emotional regulation following errors.